A new species of Graffenrieda (Melastomataceae) from the Andes in Southern Ecuador - Michelangeli, Fabián A.; Ulloa Ulloa, Carmen (Phytotaxa, 2013)
Graffenrieda penneysii, a new species known only from cloud forests in southern Ecuador is described. Graffenrieda penneysii is characterized by a calyptrate calyx that irregularly dehisces at anthesis, four-merous flowers, and indumentum of minute, sessile, glandular trichomes. This new species is compared to putative relatives in Graffenrieda and with the Andean members of Huberia due to their phenotypic resemblance. A line illustration and photograph of the type collection in the field are provided.